Effect of S-Ketamine on Postoperative Nausea and Vomiting in Patients Undergoing Video-Assisted Thoracic Surgery: A Randomized Controlled Trial - Qi Y; Zhou M; Zheng W; Dong Y; Li W; Wang L; Xu H; Zhang M; Yang D; Wang L; Zhou H (Drug Design, Development and Therapy, 2024)
Yu Qi,1– 3,* Meiyan Zhou,1– 3,* Wenting Zheng,1,2,* Yaqi Dong,1,2 Weihua Li,2,4 Long Wang,1,2 Haijun Xu,1,2 Miao Zhang,1,5 Dunpeng Yang,1,5 Liwei Wang,1– 3 Hai Zhou1– 3 1The Xuzhou Clinical College of Xuzhou Medical University, Xuzhou, Jiangsu, People’s Republic of China; 2Department of Anesthesiology, Xuzhou Central Hospital, Xuzhou, Jiangsu, People’s Republic of China; 3Jiangsu Province Key Laboratory of Anesthesiology Xuzhou Medical University, Xuzhou, Jiangsu, People’s Republic of China; 4College of Anesthesiology, Xuzhou Medical University, Xuzhou, Jiangsu, People’s Republic of China; 5Department of Cardiothoracic Surgery, Xuzhou Central Hospital, Xuzhou, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hai Zhou; Liwei Wang, The Xuzhou Clinical College of Xuzhou Medical University, Department of Anesthesiology, Xuzhou Central Hospital, Xuzhou, Jiangsu, People’s Republic of China, Email zhouhai339339@163.com; doctorlww@sina.comPurpose: Postoperative nausea and vomiting (PONV) frequently occur in patients after surgery. In this study, the authors investigated whether perioperative S-ketamine infusion could decrease the incidence of PONV in patients undergoing video-assisted thoracoscopic surgery (VATS) lobectomy.Patients and Methods: This prospective, randomized, double-blinded, controlled study was conducted a total of 420 patients from September 2021 to May 2023 at Xuzhou Central Hospital in China, who underwent elective VATS lobectomy under general anesthesia with tracheal intubation. The patients were randomly assigned to either the S-ketamine group or the control group. The S-ketamine group received a bolus injection of 0.5 mg/kg S-ketamine and an intraoperative continuous infusion of S-ketamine at a rate of 0.25 mg/kg/h. The control group received an equivalent volume of saline. All patients were equipped with patient-controlled intravenous analgesia (PCIA), with a continuous infusion rate of 0.03 mg/kg/h S-ketamine in the S-ketamine group or 0.03 μg/kg/h sufentanil in the control group. The primary outcome was the incidence of PONV. Secondary outcomes included perioperative opioid consumption, hemodynamics, postoperative pain, and adverse events.Results: The incidence of PONV in the S-ketamine group (9.7%) was significantly lower than in the control group (30.5%). Analysis of perioperative opioid usage revealed that remifentanil usage was 40.0% lower in the S-ketamine group compared to the control group (1414.8 μg vs 2358.2 μg), while sufentanil consumption was 75.2% lower (33.1 μg vs 133.6 μg). The S-ketamine group demonstrated better maintenance of hemodynamic stability. Additionally, the visual analogue scale (VAS) scores on postoperative day 1 (POD-1) and postoperative day 3 (POD-3) were significantly lower in the S-ketamine group. Finally, no statistically significant difference in other postoperative adverse reactions was observed between the two groups.Conclusion: The results of this trial indicate that perioperative S-ketamine infusion can effectively reduce the incidence of PONV in patients undergoing VATS lobectomy.Keywords: S-ketamine, postoperative nausea and vomiting, hemodynamics, non-opioid analgesic, postoperative pain, video-assisted thoracoscopic surgery lobectomy